Perancangan Enterprise Architecture Sistem Informasi Naskah Kebijakan Strategi Nasional Menggunakan TOGAF ADM (Studi Kasus: Setjen Wantannas RI) - Nugroho, Adi; Sari , Agustin Rusiana (Syntax Literate, 2025)
The Secretariat General of the National Resilience Council (Setjen Wantannas RI) plays a strategic role in formulating national policies to support Indonesia's national resilience. The information system supporting the process of formulating national strategic policies currently faces several challenges, including a lack of system integration, inefficient data management, and limited supporting technology. This study aims to design an information system architecture based on TOGAF ADM to improve the efficiency and accuracy of data management in the formulation of national strategic policy documents. Using a case study approach and in-depth interviews with policymakers, executors from four deputies of Setjen Wantannas, and practitioners, this research produces an information system architecture blueprint covering business processes, data, applications, and technology. This blueprint serves as a strategic guide to enhance efficiency, data accuracy, accelerate decision-making, and strengthen coordination among ministries and agencies in the formulation of national strategic policies.